Fibroblast growth factor-10 maintains the survival and promotes the growth of cultured goat preantral follicles - Chaves, R. N.; Lima-Verde, I. B.; Celestino, J. J. H.; Duarte, A. B. G.; Alves, A. M. C. V.; Matos, M. H. T.; Campello, C. C.; Name, K. P. O.; Bao, S. N.; Buratini, J. [UNESP]; Figueiredo, J. R. (Elsevier B.V., 2010)
The aim of the present study was to investigate the effects of fibroblast growth factor-10 (FGF-10) on the survival, activation (transition from primordial to primary follicles), and growth of goat preantral follicles cultured in vitro. Pieces of ovarian cortex were cultured for 1 and 7 d in the absence or presence of FGF-10 (0, 1, 10, 50, 100, and 200 ng/mL). Noncultured and cultured tissues were processed and analyzed by histology, transmission electron microscopy, and viability testing. Results showed that after 7 d, a greater percentage (79.9%) of morphologically normal follicles (containing an oocyte with regular shape and uniform cytoplasm, and organized layers of granulosa cells without a pyknotic nucleus) was observed when cultured with 50 ng/mL of FGF-10 when compared with other concentrations of FGF-10 (0 ng/mL, 67.3%; 1 ng/mL, 68.2%; 10 ng/mL, 63.3%; 100 ng/mL, 64.4%; 200 ng/mL, 52.7%). Ultrastructural analyses and viability testing using fluorescent markers confirmed the follicular integrity of FGF-10 (50 ng/mL)-treated fragments after 7 d of culture. After 7 d, all FGF-10 concentrations reduced the percentage of primordial follicles and increased the percentage of developing follicles. In the presence of 50 ng/mL of FGF-10, follicles increased in diameter after 7 d of culture when compared with other concentrations tested. In conclusion, this study demonstrates that FGF-10 maintains the morphological integrity of goat preantral follicles and stimulates the growth of activated follicles in culture. The culture conditions identified here contribute to the understanding of the factors involved in goat early follicular development. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Goat; early follicles; viability; ovary; FGF-10